Investigating the effectiveness of oral ketamine on pain, mood and quality of life in treatment resistant chronic pain - Al Mukhaizeem, Sammy; Nasa, Anurag; Waldron, Dympna; McDaid, Alex; Gorman, Patrick J.; Featherstone, Molly; Barry, Megan; Murphy, Paul; Gallagher, Hugh; Nair, Shrijit; O’Connor, Michael; Kelly, Linda; et al. (Frontiers in Pain Research, 2023)
Introduction Chronic pain is defined as pain lasting longer than 3 months. This often causes persistent emotional distress and functional disability that is refractory to conventional treatments. Emerging evidence suggests that oral Ketamine therapy may have a specific role in managing treatment-resistant chronic pain. This study aimed to assess the effectiveness of oral ketamine within a tertiary chronic pain management clinic. Methods This study was a clinic-based retrospective descriptive study of 79 patients with a broad range of chronic pain diagnoses and treated with oral ketamine over a period up to 12 years. Changes in pain, mood and quality of life (QoL) were assessed using a numerical pain severity score, the Brief Pain Inventory (BPI), the Public Health Questionnaire (PHQ-9) and American Chronic Pain Association Quality of Life (QoL) scale. Results 73 patients were accessible for follow-up (mean daily dose and treatment duration were 193.84 mg and 22.6 months respectively). Pain scores decreased (p < 0.0001) on both numerical scores (41.6% decrease) and BPI scoring (mean decrease 2.61). Mood improved (p < 0.0001) across both PHQ-9 and BPI measurements. Patients also reported less difficulty with daily activities and improved QoL. The most common adverse reaction was drowsiness (21.9%), with 30.1% reporting no adverse reactions from Ketamine. Discussion This work adds to the growing body of evidence that under the supervision of a pain specialist, oral ketamine therapy may be a safe, tolerable and effective treatment for chronic pain conditions which have not responded to other management options. Further research is required to produce a more accurate understanding of its chronic use. Key message This real-world study shows that patients being treated with oral ketamine for chronic pain report decreased severity of pain, improved mood and increased quality of life across all conditions.